2010
DOI: 10.1016/j.neuroimage.2010.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-dependence of surround suppression in Macaque V1: Experimental testing of a recurrent network model

Abstract: Neuronal responses in primary visual cortex (V1) to optimally oriented high-contrast stimuli in the receptive field (RF) center are suppressed by stimuli in the RF surround, but can be facilitated when the RF center is stimulated at low contrast. The neural circuits and mechanisms for surround modulation are still unknown. We previously proposed that topdown feedback connections mediate suppression from the "far" surround, while "near" surround suppression is mediated primarily by horizontal connections. We im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 58 publications
(147 reference statements)
10
70
0
Order By: Relevance
“…Contrast normalization has been successfully used to model surround suppression (Carandini and Heeger 2012). In primate and cat V1, spatial and temporal properties of center-surround interactions depend on stimulus contrast (Kapadia et al 1999;Sadakane et al 2006;Sceniak et al 1999;Schwabe et al 2010;Webb et al 2005). In the present study, we have shown that stimulus contrast similarly influences surround suppression in mouse V1, where lower stimulus contrast leads to larger RF center sizes and weaker suppression strength (see also Ayaz et al 2013;Nienborg et al 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Contrast normalization has been successfully used to model surround suppression (Carandini and Heeger 2012). In primate and cat V1, spatial and temporal properties of center-surround interactions depend on stimulus contrast (Kapadia et al 1999;Sadakane et al 2006;Sceniak et al 1999;Schwabe et al 2010;Webb et al 2005). In the present study, we have shown that stimulus contrast similarly influences surround suppression in mouse V1, where lower stimulus contrast leads to larger RF center sizes and weaker suppression strength (see also Ayaz et al 2013;Nienborg et al 2013).…”
Section: Discussionsupporting
confidence: 58%
“…For certain strengths the predicted suppression is within the 50% confidence region while for others it is outside. This study shows that one can respect the variability in the data in terms of heterogeneity of the underlying microcircuits and still use experimental data with NMM-like network models in order to learn something about the actual microcircuits: Here, we found that within the class of models we considered the models with stronger feedback projections to inhibitory neurons in the model V1 produce quantitatively better matches to the measured surround suppression than models with less feedback to these inhibitory neurons; see Schwabe et al (2010) for more details. Of course, stochastic models respecting heterogeneity in single cell properties and network connections, or models for large-scale simulations could be described with model parameters , which capture such heterogeneity and hence would be directly useable within a Bayesian model comparison.…”
Section:  mentioning
confidence: 76%
“…In our modeling of visual cortical networks we also employed mean-field firing rate models as in NMMs (as well as more detailed models with so-called "spiking neurons"). We could show that single neuron responses in primary visual cortex (V1) are best explained when the local cortical microcircuits are assumed to operate in a balance between strong recurrent excitation and inhibition (Mariño et al, 2005a;Stimberg et al, 2009), and that inter-areal feedback into V1 may play a crucial role in "lateral inhibition" (Schwabe et al, 2006a;Ichida et al, 2007;Schwabe et al, 2010). To the best of our knowledge, such and other recent advances in cortical microcircuits models have not yet been implemented into NMMs used in brain imaging.…”
Section: Selected Advances In Cortical Microcircuit Modelsmentioning
confidence: 99%
See 2 more Smart Citations